CARACTERIZACIÓN DE LOS ESTILOS DE ENSEÑANZA EN LA EDUCACIÓN SUPERIOR (2016)
This article is based on an investigation developed as part of the Teacher Professional Development Program from the Rodrigo de Bastidas Law School, Santa Marta sectional, Colombia. It aimed: Identify and analyze the principal characteristics that guide teaching practices in the Law School, to elaborate a profile of teaching styles and use it to create a capacitation programs.By means of a qualitative methodology approach that articulated the quantitative and qualitative information, it was designed a poll formed by ten (10) dimensions, with thirteen (13) items and seventy five (75) affirmations; it was identified and analyzed the teaching styles of the sixty nine teachers who participated in sample, from beliefs, the concepts facing the instructional tasks and management of pedagogic activity.The investigation ratifies the recognition to the special characteristics of each teacher who participated in sample highlighting human diversity and difference. Regarding teaching styles, by one side is emphasized, that there isn’t only one profile of teaching styles (misted styles); coexist heterogeneous styles, it is shown by the different wealth in the way of teaching and by other side, the teachers shares common points of view, thus establishing distinct profiles and teaching styles.